A porous biomass-derived anode for high-performance sodium-ion batteries. (April 2018) - Zhu, Youyu; Chen, Mingming; Li, Qi; Yuan, Chao; Wang, Chengyang
Abstract: Although hard carbons have been turned out to be suitable for sodium storage, their high cost and low initial coulombic efficiency (ICE) need to be addressed for the commercial application. Here, we report an effective route including a pyrolysis process and a reductive strategy to synthesize high-performance hard carbons from waste apricot shell. The obtained hard carbons inherit the unique architecture of the apricot shell, delivering a large interlayer spacing and a well-connected structure, which are beneficial for the Na + intercalation and transport. The anode performance is further enhanced by H2 reduction treatment, which efficiently reduces the defects and thus improves the ICE. The final prepared hard carbons exhibit a promising anode performance with a desirable reversible capacity of ca . 400 mAhg −1, an improved ICE of 79% and an excellent cycling stability. This study should contribute to the better utilization of the biomass waste for the future large-scale application of sodium-ion batteries. Graphical abstract: Image 1